PROMOTING LECTURER WELL-BEING THROUGH RESILIENCE: A CONCEPTUAL FRAMEWORK FOR ADDRESSING BURNOUT - Hussein, Kamariah; Ali, Fariha Diyana Awang; Radzi, Nadiah Hashim (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
The escalating rates of burnout among lecturers pose a significant threat to staff well-being, professional longevity, and the overall performance of higher education institutions. In response, this conceptual paper develops a multi-dimensional framework for fostering lecturer resilience. Grounded in recent literature (2020–2025), the framework synthesizes three core domains: psychological (emotional intelligence, mindfulness), professional (mentorship, reflective practices), and institutional (supportive culture, workload clarity). It argues that resilience is a malleable construct, developed through a combination of self-care routines and enabling environments, rather than an innate trait. The paper further specifies the responsibility of institutions to embed mental health policies, promote work flexibility, and champion inclusive cultures. Strategies for evaluating and refining the framework through a mixed-methods lens are also provided. By shifting the focus from reactive stress management to proactive resilience-building, this paper offers a vital guide for educational leaders dedicated to sustaining faculty well-being in a demanding academic world.